Developing and evaluating strategies to implement an insulin patient decision aid in an academic primary care clinic in Malaysia / Tong Wen Ting - Tong, Wen Ting (2021)
Patient decision aids (PDAs) are decision-making tools to facilitate shared decision-making; however, their routine use in clinical consultations is still lacking. This study aims to develop and evaluate strategies to effectively implement a locally developed insulin PDA in an academic primary care clinic in Malaysia. This implementation study began with a qualitative exploration to identify PDA implementation barriers in Malaysian public healthcare settings (Phase 1). In Phase 2, an implementation intervention was systematically developed for the insulin PDA in an academic primary care clinic. This involved stakeholders using a multi-voting technique to prioritise Phase 1 barriers. Next, strategies were identified to overcome the prioritised barriers based on evidence, pragmatic suggestions from clinic stakeholders, and implementation taxonomies. The intervention was finalised through a clinic stakeholders meeting. In Phase 3, a mixed-methods evaluation was conducted to assess implementation outcomes guided by the ‘Reach’, ‘Adoption’, ‘Implementation’, and ‘Maintenance’ dimensions of the RE-AIM framework. In Phase 1, unique and prominent barriers to the insulin PDA implementation were found in the Malaysian healthcare settings such as role boundary, the lack of continuity of care, the lack of SDM culture, language barrier, and patient literacy level. In Phase 2, 13 barriers were prioritised and they were related to healthcare providers’ (HCP) roles, patient’s characteristics and attitudes, and follow-up difficulties. Eleven strategies including training, feedback, PDA availability, and systematic documentation were integrated into an implementation intervention to address the barriers. The outcomes showed that for ‘Reach’, 88.9% of the doctors received PDA training and this was attributed to their self-motivation, mandated changes, and timing of the PDA workshop. The PDA reached 387 patients and was facilitated by the doctors who delivered the PDA to them and their own desire to know more about insulin. Barriers to reaching patients were their attitudes towards their health, and lack of interest to initiate iv insulin. Doctors’ adoption of the PDA was high (83.3%) and was attributed to their positive experience with the PDA use, its usefulness, and the training workshop effectiveness. Barriers to adoption were patients’ non-use of the PDA, availability of doctors in the clinic, and the lack of effectiveness of the strategy ‘Provide feedback’. Patients’ adoption was moderate where only 65.7% read the given PDA. Among the reasons for not reading the PDA were a lackadaisical attitude towards their health, and perceived adequate knowledge about diabetes and insulin. The degree of ‘Implementation’ of the PDA varied for different tasks and was challenging for reasons such as the perception of unnecessary steps, the clinic’s appointment system, and nurses’ attitudes. Finally, for ‘Maintenance’, 80% of the doctors were willing to continue using the PDA due to its benefits. In conclusion, this study outlines a systematic process of developing PDA implementation intervention. When implementing PDAs, it is crucial to consider the healthcare culture and system. Focusing on implementation efforts such as training to improve providers’ knowledge and skills, organisational leaders’ support and utilising a documentation system to facilitate follow-ups can lead to a higher reach and adoption of PDAs. Keywords: Implementation, Implementation research, Patient decision aids, Shared decision making, Type 2 diabetes mellitus